Results of receiver operating characteristic curve analysis (subgroup analysis of cases where the time window between the diuretic renal scintigraphy and ultrasound is ≤ 90 days). - Dheeratama Siripongsatian (21387371) (2025)
Results of receiver operating characteristic curve analysis (subgroup analysis of cases where the time window between the diuretic renal scintigraphy and ultrasound is ≤ 90 days).